Công văn của Bộ Nội vụ về việc Báo cáo thực hiện Nghị quyết 33/2016/QH14 Quốc hội khóa XIV - Bộ Nội vụ (2017)
Công văn của Bộ Nội vụ về việc Báo cáo thực hiện Nghị quyết 33/2016/QH14 Quốc hội khóa XIV (Số: 2304/BNV-VP) ngày 28/04/2017.